The Analysis of Sustainable Firm Performance in Textiles SMEs in Bogor, Indonesia - Liestyana, Yuli; Adella, Nabila Prisma; Wahyuningsih, Tri; Utami, Yekti (Journal of Management and Business Review, 2024)
Green supply chain management (GSCM) is an environmentally friendly initiative for all stages of the product life cycle, from product design to handling when the product life cycle ends. This research aims to determine the impact of green entrepreneurial orientation, market orientation, and green supply chain management practices on sustainable firm performance. The sample used was textile SMEs in Bogor Regency, with 62 respondents. The technique used for sampling is purposive sampling with the criteria of SMEs applying the green supply chain management concept. Data was collected through a questionnaire and analyzed using PLS (Partial Least Square). The study shows that green entrepreneurial orientation does not affect green supply chain management practices. Market orientation influences green supply chain management practices. Green supply chain management practices influence sustainable firm performance. Green supply chain management practices do not mediate the relationship between green entrepreneurial orientation and sustainable firm performance but do mediate the relationship between market orientation and sustainable firm performance.